Overcoming AIDS : lessons learned from Uganda - Morisky, Donald E.; Jacob, W. James; Nsubuga, Yusuf K.; Hite, Steven J. (Research in global child advocacy (Unnumbered), 2006)
As a result of the AIDS epidemic, many nations around the world have faced the demands of caring for a particularly vulnerable population of children, the orphans of parents who have died of AIDS or whose caregivers are terminally ill from the disease. Overcoming AIDS: Lessons Learned from Uganda offers an in-depth exploration of this global issue and provides a broad focus on evolving a constructive response to the HIV/AIDS epidemic. This collaborative resource is the fourth in the Research in Global Child Advocacy book series, and it offers readers a glimpse into the experience of HIV/AIDS infected and affected people from the perspective of researchers, policy makers, and professionals who diligently work toward crafting a framework for action that is integrated across disciplines. Despite the enormity and intensity of the problem, chapter authors share a commitment to advocate for a better world in which social and economic disparities do not preclude children from experiencing a future that is bright with potential opportunities and hope.